Congenital Gerbode defect in an adult patient report of an extremely rare case - Díaz-Sarasa, Pedro Daniel (2023)
Gerbode Defect (GD) is a rare congenital heart disease that mainly affects the upper portion of the membranous septum, generating a shunt between the left ventricle and the right atrium. Even though most cases are congenital, it has also been reported acquired cases due to cardiac surgery, infective endocarditis, acute ischemic heart disease, and invasive percutaneous procedures. The diagnostic workup includes the clinical evaluation and the echocardiographic study. Here, we present the case of a 43-year-old adult patient with an incidental finding of a congenital GD in the context of acute appendicitis. Imaging plays a role in the diagnostic workup of congenital diseases; in this case, it allowed us to identify more details and the decision-making for our patient.